Determination Digital Economy of Strengthen Local Halal Tourism - Al Kautsar, Syahvergio Anugrah; Ma’adi, Alan Su’ud; Rohman, Taufiqur (Ulumuna: Jurnal Studi Keilsman, 2023)
The digitalization transformation of halal tourism in Indonesia is categorized as low. This study aims to reveal the influence of variables, security, fintech, brand image and infrastructure on people's decisions to travel halal in Madura. This type of research was sourced from primary data obtained from the distribution of questionnaires in the coastal area of Madura, the meeting of 100 respondents based on the calculation of Lemeshow. Multiple linear regression analysis method used SPSS 24 Software to analyze this research data. The results of the study include security fintech influence Sig. (0.005) on people's decisions to travel halal in Madura, infrastructure and brand image influence Sig. (<0.005) on people's decisions to travel halal in Madura. Based on these results, it encourages further research to analyze different factors that influence people's decisions in halal local tourism in Madura.